2019
DOI: 10.1177/0021998319871354
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on impact, sound, and vibration response of natural-based composite sandwich made of flax and agglomerated cork

Abstract: In recent years, material scientists have been focusing on the utilization of materials from natural resources due to environmental concerns. In the same context, the aim of this work is to evaluate impact response, sound absorption behavior, and vibration damping characteristics of natural-based composite sandwich made of flax as skin reinforcement and agglomerated cork as core. Vacuum bagging method was used for manufacturing composite sandwiches with different cork densities of 240, 280, and 340 kg/m3. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Other applications are in the field of acoustics for the automobile industry. 25,26 The materials reinforced with natural fibres have certain advantages compared to the traditional ones because they come from renewable resources, they are largely available, light and are not harmful in their processing. In addition, the reinforcements do not produce irritations or other effects on safety and health during management.…”
Section: Introductionmentioning
confidence: 99%
“…Other applications are in the field of acoustics for the automobile industry. 25,26 The materials reinforced with natural fibres have certain advantages compared to the traditional ones because they come from renewable resources, they are largely available, light and are not harmful in their processing. In addition, the reinforcements do not produce irritations or other effects on safety and health during management.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Furthermore, the extraction and observation of the water body from the remote sensing data lead to easily and correctly determine various water resources monitoring, management, wetland classification, water/land cover segmentation, and coastline of lake detection. [5][6][7][8] This work aims to determine the Mosul Dam reservoir water case and monitor the quality of water and its impact on human health due to environmental and climatic changes that had occurred in recent years, which caused decline of water quantity and increase in pollution and sedimentation, which has been tested over a 31-year period. Thus, using temporal remote sensing data is the best choice for this work to observe the changing over the mentioned period.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the use of the materials, sandwich panels may be natural, hybrid, or fully synthetic. There are several studies reported in the literature about natural and hybrid sandwich structures, constructed with various materials, but only a few of these assess the sandwich panel's acoustic properties [10][11][12][13]. The majority of them focuses on mechanical strength.…”
mentioning
confidence: 99%
“…These structures are mainly used in engineering, automotive, and aeronautical applications. The skins are mainly produced from hardwood plates [14], veneer [15], flax fibers-epoxy resin composite [10,12], bamboo, and cotton bound with a vinyl ester matrix [11], natural silk fiber and epoxy resin [16], glass fiber mat [17,18], aluminum sheets [19,20], and carbon fiber-epoxy resin composite [13]. Similarly, the core of the structures could be prepared from mushroom foam [14], agglomerated cork [10,13], balsa wood [11,12], pine wood [11], medium density fiberboard [20], a textile fibers-bone glue composite [15], natural fibers (palm leaf, coconut, raffia, oil palm) and polyester resin [17], natural fibers (jute and hemp) and epoxy resin [18,19], and synthetic foams [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation